(untitled) (Swiss Medical Weekly, 2024)
BACKGROUND: While patient and public involvement (PPI) in clinical research contributes substantially to research ethics, feasibility and quality, the uptake and implementation of PPI-based approaches in Switzerland remain unknown. This study aimed to evaluate the current state and acceptance of PPI in academic clinical research in Switzerland, with the goal of developing recommendations for its future implementation and development. METHODS: A sequential explanatory mixed-methods study was conducted to assess the current landscape and acceptance of PPI in academic clinical research across different stakeholder groups in Switzerland. The groups were “Patients and Public”, “Researchers”, “Staff Members of Academic Research Infrastructure (ARI)” and representatives from “Regulatory and Funding Bodies”. Data was collected through a combination of surveys and semi-structured interviews. The survey results were analysed descriptively, while interview data was analysed qualitatively. The results were further synthesised into a SWOT (Strengths, Weaknesses, Opportunities and Threats) analysis. RESULTS: A total of 123 survey responses were collected.Surveys revealed great support and acceptance for PPI in academic clinical research in Switzerland across all stakeholder groups. Despite this support, several challenges were identified, including gaps in training, limited funding opportunities and insufficient infrastructure to facilitate PPI. CONCLUSION: The current framework for PPI in Switzerland is in an early stage of development. A joint effort by all stakeholders is needed to catch up with international progress to reach high-level ethical and quality standards. A basic framework for PPI in academic clinical research in Switzerland should be implemented, including guidelines for qualification and collaboration, best practices as well as widespread information for patients, the public and researchers. Further needed are training opportunities in “PPI in clinical research” for all stakeholders as well as sustainable sources of funding.